Galectin-1 Markedly Reduces the Incidence of Resorptions in Mice Missing Immunophilin FKBP52 - Hirota, Yasushi (Endocrine Society, 2012)
Progesterone (P(4)) signaling is critical for pregnancy. We previously showed that immunopilin FK506 binding protein (FKBP)52 serves as a cochaperone to optimize progesterone receptor (PR) function in the uterus, and its deficiency leads to P(4) resistance in a pregnancy stage-specific and genetic background-dependent manner in mice. In particular, sc placement of SILASTIC implants carrying P(4) rescued implantation failure in CD1 Fkbp52(−/−) mice, but the resorption rate was substantially high at midgestation due to reduced P(4) responsiveness. Because downstream targets of P(4)-FKBP52-PR signaling in the uterus to support pregnancy are not clearly understood, we performed proteomic analysis using Fkbp52(−/−), PR-deficient (Pgr(−/−)), and wild-type (WT) uteri. We found that the expression of galectin-1 (Gal1), an evolutionarily conserved glycan-binding protein, was significantly down-regulated in both Fkbp52(−/−) and Pgr(−/−) uteri compared with WT uteri. During early gestation, Lgals1, which encodes Gal1, was distinctly expressed in stromal and decidual cells. Lgals1 expression was much lower in d 4 Fkbp52(−/−) uteri compared with WT uteri, and this reduction was reversed by P(4) supplementation. More interestingly, concomitant supplementation of recombinant Gal1 significantly suppressed the high resorption rate and leukocyte infiltration at implantation sites in CD1 Fkbp52(−/−) females carrying P(4) SILASTIC implants. These findings suggest that uterine Gal1 is an important downstream target of P(4)-FKBP52-PR signaling in the uterus to support P(4) responsiveness during pregnancy.